Unveiling the Therapeutic Potential of Bauhinia racemosa High-Throughput Screening for Hypoxia-Induced Receptor Inhibitors in Sickle Cell Disease (SCD) - Khan, Mohammad Nadeem; Bhandari, Mahak; Vyas, Sanjay; Upadhayay, Shushil; Dubey, Praveen Chandra (Free Radicals and Antioxidants, 2025)
Background: Sickle Cell Disease (SCD) is a major genetic disorder with significant morbidity and mortality, particularly among tribal populations in Madhya Pradesh, India. The prevalence of sickle cell hemoglobin among these communities ranges from 10-33%, with about 0.7% suffering from SCD. Hypoxia plays a central role in the pathophysiology of SCD, and the inhibition of Hypoxia-Inducible Factor (HIF) Prolyl Hydroxylase (PHD) proteins has emerged as a promising therapeutic strategy. Aim and Objectives: This study investigates Bauhinia racemosa's ethnomedicinal uses in Central India, screens its phytochemicals for inhibitory activity against HIF-PHD proteins, and evaluates their binding affinity, stability, and interactions through in silico docking, comparing results with standard inhibitors like Desidustat. Materials and Methods: Ethnobotanical fieldwork in Alirajpur, Jhabua, and Dhar identified medicinal uses of Bauhinia racemosa. Twelve bioactive compounds were screened and evaluated via in silico docking, RMSD analysis, and receptor-ligand interaction studies, comparing them with known HIF inhibitors. Results: Out of the twelve screened phytochemicals, compounds such as Quercetin, Stigmasterol, and 3-O-Methylquercetin exhibited high binding affinity scores ranging from -10.7 to -12.9 kcal/ mol, surpassing the standard inhibitors like Desidustat (-9.7 kcal/mol). RMSD analysis showed these phytochemicals formed stable complexes with the HIF-PHD receptor. Strong hydrogen bonding and hydrophobic interactions further enhanced the receptor-ligand binding stability, indicating a high therapeutic potential. Conclusion: Bauhinia racemosa phytochemicals exhibit strong inhibitory potential against HIF-PHD proteins, demonstrating superior binding affinity and stability compared to standard inhibitors, offering promising therapeutic prospects for hypoxia-related disorders.
Keywords: Bauhinia racemosa; Hypoxia-inducible factor; HIF Prolyl hydroxylase; Molecular; docking; Receptor-ligand interactions; Phytochemicals; Ethnomedicinal knowledge; Drug; discovery; Hypoxia-related disorders